Reliability of Dynamic Kinematic Accuracy for Gear Transmission - Peng Xiao Tiyi Liu Tao Zhang Junfu Peng (Jixie chuandong)
Gears are important components of mechanical products and its motion accuracy directly affects the quality and reliability of machinery. The influence factors of gear transmission accuracy include gear manufacturing， assembly errors and external loads， all of which are stochastic. Therefore， it is an important way to improve the motion accuracy of gear transmission by reliability analysis and design under the uncertainty design theory. In order to carry out reliability analysis of gear transmission accuracy， a torsional vibration model of a pair of gear is established with transmission error excitation，stiffness excitation and external load. Then， the four order Runge-Kutta method is used to solve the dynamic response of gear transmission， BP neural network is applied to build the input-output relationship model of dynamic system and motion accuracy reliability model of gear transmission system is then created. Finally，the first-order reliability method（FORM） is used to solve the motion reliability of the transmission system. The results show that the manufacturing and assembly errors are important factors affecting the reliability of the kinematic accuracy of the driving mechanism，which should be fully considered in the design and manufacture of gears.